The Influence of Dividend Policy, Investment Decisions and Funding Decisions on the Value of Infrastructure, Utilities & Transportation Companies Listed on the IDX for the 2019-2021 Period - Dwi Rizqi Amalia; Hartono; Yuliasnita Verlandes (International Journal of Management and Business Economics, 2023)
The company as an economic entity has short term and long term goals, in the short term the company aims to generate maximum profits and the long term goal is to increase the value of the company. The Covid-19 pandemic in Indonesia affected the business management of a company in the infrastructure, utilities and transportation sector, which experienced a decline in company performance. Company value as measured by Price Book Value (PBV) for the infrastructure, utilities and transportation sectors has fluctuated from 2019 – 2021. Internal factors include dividend policy, investment decisions and funding decisions. To determine the effect of dividend policy, investment decisions and funding decisions on firm value is the aim of this study. This type of research is a quantitative approach. This study uses secondary data taken through the IDX data website. Sampling method used is purposive sampling. The sample used in this research is 13 companies consisting of the infrastructure, utilities and transportation sectors which are listed on the Indonesia Stock Exchange for the 2019-2021 period. The data analysis technique uses multiple linear regression analysis with the SPSS 25 program. Based on the results of the study, it shows that the dividend policy variable has no effect on firm value, investment decisions have a positive and significant effect on firm value and funding decisions have a significant negative effect on firm value.